La recherche des exposants caractéristiques pour le Système du deux équations homogenes diférentielles - Golokvosčius, P. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:П. Голоквосчюс. Отыскание характеристических показателей системы двухлинейных однородных дифференциальных уравненийP. Golokvosčius. Dviejų tiesinių homogeninių diferencialinių lygčių sistemos charakteringųjų rodiklių radimas